2016
DOI: 10.1017/s0950268816000674
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the incidence of MRSA patients: evaluation of a surveillance system using health insurance claim data

Abstract: SUMMARYBecause sentinel surveillance systems cannot obtain information about patients who visit non-sentinel medical facilities, the characteristics of patients identified by these systems may be biased. In this study, we evaluated the representativeness of a methicillin-resistant Staphylococcus aureus (MRSA) surveillance system using health insurance claim (HIC) data, which does not depend on physician notification. We calculated the age-specific incidence of MRSA patients using data from the Japan Nosocomial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…An analysis of the potential for sampling bias in the 30 studies [ 12 , 18 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ] that used retrospective analysis of routinely collected data revealed that the rationale for the choice of the time period and the geographic area was not provided in all studies. Furthermore, the studies did not all include a description of who had collected and analysed the data and whether they had an affiliation with the programme (i.e., whether they were independent or not).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An analysis of the potential for sampling bias in the 30 studies [ 12 , 18 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ] that used retrospective analysis of routinely collected data revealed that the rationale for the choice of the time period and the geographic area was not provided in all studies. Furthermore, the studies did not all include a description of who had collected and analysed the data and whether they had an affiliation with the programme (i.e., whether they were independent or not).…”
Section: Resultsmentioning
confidence: 99%
“…Representativeness was included in only three evaluations [ 13 , 16 , 38 ], all using retrospective analysis of routinely collected data. An evaluation of a methicillin-resistant Staphylococcus aureus (MRSA) surveillance system in Japan using health insurance claims [ 38 ] observed that the surveillance system was accurately representing the ages of patients. Saeed et al [ 13 ] observed that the HMIS in Afghanistan only included public health facilities with no data from the private sector (which it was attempting to cover).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Japan has reached out to many countries in the region (eg, Indonesia and India) by offering the JANIS software to support national AMR surveillance. 12 13 14 …”
Section: It Based Amr Surveillance: Examples From Sweden and Japanmentioning
confidence: 99%
“…Antimicrobial-resistant bacteria pose a major global health problem because treatment options are extremely limited. 1) In 2015, the WHO proposed that all member countries establish a national action plan for countering antimicrobial resistance (AMR). 2) In Japan, the Ministry of Health Labour and Welfare formulated a national action plan on AMR in 2016, and the monitoring of antibiotic use and resistant bacteria has been strengthened since then.…”
Section: Introductionmentioning
confidence: 99%